The cost and emission saving potential of wind power - Ferreira, Paula Varandas (2013)
This paper addresses the effect of the increasing wind penetration on the operating performance of a diversified electricity system comprising wind, thermal, hydro and other renewable power plants. A short term optimization model is used to run the exploration planning under different wind power scenarios. The seasonality of the hydro and wind regimes and the hourly variations of supply and demand are acknowledged in the model. Simulations for the Portuguese electricity system are presented in order to establish the use of the proposed model on supporting more informed decision making for future energy strategies. The cost savings and CO2 abatement potential of wind power are estimated along with the effects on the operating performance and costs of thermal power plants.